Notas sobre o perigo - Migliari, Wellington (Opiniães, 2014)
This article is devoted to an analysis of the “Proposta Curricular do Estado de São Paulo – Ensino Fundamental II e Ensino Médio” for Portuguese. Not only have we tried to point out the negative elements of a State project concerning literature, but also the denial of the literary learning as a possible emancipation experience. An introduction to numbers and statistics showing the failure of learning architected by the educational public system in the state of São Paulo seems to be really illustrative, as well. After a brief critical discussion involving literature and experience, we try to think about some of Tzvetan Todorov’s ideas and the question of literary form in Literatura em perigo. Even in a different culture and reality, the presumption of the critic may permit us to denounce a negative process underlying the present educational values in the “Proposta Curricular”. We can also advance in the topic of literary education making some considerations about labour class and work, respectively, symbols of alienation and social positive construction.